O impacto dos programas DOBES, DMA E AILLA sobre a questão das línguas indígenas ameaçadas: uma abordagem crítica e proposta básica de um projeto de arquivo linguístico para o setor de linguística do Museu Nacional - Albuquerque, Luiz Claudio Falcão de (2023)
This dissertation has as a general objective to investigate, critically, the impact of the language documentation programs Dokumentation Bedrohter Sprachen (DOBES), Digital Media Archive (DMA) and Archive of Indigenous Languages of Latin America (AILLA) from their structuring processes to address the problem related to endangered indigenous languages. For this purpose, the idea is to assess, broadly, how the set of initiatives adopted can be validated or not as efficient policies around the desired interests. In terms of theoretical referential, we use material from the most recent publications related to our research object. About the methodology, we adopt the essential elements divided into categories according to: the purpose (applied research), the approach (qualitative- quantitative research), the method (hypothetical deductive) and the procedures (bibliographical research). About the result of what was analyzed about the object, it can be stated that the linguistic documentation programs studied act with professionalism, are consolidated and have reached their goals in terms of documentation, storage and availability of linguistic archives to the general public. The impact of the DOBES, DMA, and AILLA programs on the issue of endangered indigenous languages is positive, as they can be considered relevant in the effort to avoid an irreparable linguistic and cultural catastrophe for indigenous peoples in particular, and for humanity in general. Thus, the relative success of the documentation programs investigated has compelled us to make a basic project proposal of a digital linguistic archive for the Linguistics Sector of the National Museum/UFRJ, with the intention of having it, in the future, materialized in a web system that will contribute to provide teachers, researchers, students and speech communities with an adequate place for storing, consulting and sharing, online, all the content of the primary data from their field research in documentary linguistics. Keywords: DOBES, DMA and AILLA programs. Endangered indigenous languages. A critical approach. Linguistic archive Project.